Effects of gut microbiota and probiotics on Alzheimer’s disease - Guo Libing; Xu Jiaxin; Du Yunhua; Wu Weibo; Nie Wenjing; Zhang Dongliang; Luo Yuling; Lu Huixian; Lei Ming; Xiao Songhua; Liu Jun (Translational Neuroscience, 2021)
Alzheimer’s disease (AD) is a progressive neurodegenerative disease with high morbidity, disability, and fatality rate, significantly increasing the global burden of public health. The failure in drug discovery over the past decades has stressed the urgency and importance of seeking new perspectives. Recently, gut microbiome (GM), with the ability to communicate with the brain bidirectionally through the microbiome–gut–brain axis, has attracted much attention in AD-related studies, owing to their strong associations with amyloids, systematic and focal inflammation, impairment of vascular homeostasis and gut barrier, mitochondrial dysfunction, etc., making the regulation of GM, specifically supplementation of probiotics a promising candidate for AD treatment. This article aims to review the leading-edge knowledge concerning potential roles of GM in AD pathogenesis and of probiotics in its treatment and prevention.